Real-world challenges in hepatocellular carcinoma in Central America and the Caribbean: insights from a multinational expert survey - Perelló, Christie; Disla, Hugo J.; Coste, Pablo; Valdez, Marisabell; Páez, Dayron; Rivera, Carlos; Loo, Yong; Mayorga, Tania; Torres, Kenia; Pol, Edwyn; Adames, Enrique; Mayo, Miguel; et al. (Frontiers in Oncology, 2025)
Hepatocellular carcinoma (HCC) represents a growing public health concern in Central America and the Caribbean, yet regional data on its management remain limited. A cross-sectional descriptive survey was conducted among 51 liver cancer specialists across nine countries, exploring four domains: epidemiology, screening, diagnostics, and treatment access. Analysis of the 20-item questionnaire revealed significant disparities in HCC care across the region. National cancer registries and structured screening programs were largely absent. Although ultrasound was widely available, its routine use for surveillance was inconsistent, and radiologist training levels varied. Access to diagnostic imaging such as triphasic computed tomography and magnetic resonance imaging was uneven. While liver surgery was generally accessible, liver transplantation was limited to Costa Rica and, to a lesser extent, the Dominican Republic. Systemic therapies such as sorafenib and lenvatinib were commonly available, However, access to first-line immunotherapy was constrained by limited insurance coverage and delayed governmental approval. In several countries, fewer than 30% of patients received treatment approval, with delays exceeding five months. Multidisciplinary tumor boards were not routinely implemented. In conclusion, these findings provide the first regional overview of HCC management in Central America and the Caribbean, underscoring critical gaps in surveillance infrastructure, diagnostic capacity, therapeutic access, and institutional coordination. Addressing these gaps is essential to improving liver cancer outcomes and equity across the region.